Sensor Injection Based Routing Protocol for Effective Load Balancing in Underwater Wireless Sensor Networks - Yadav P.; Yadav S.; Srivastava A.; Gupta S.K.; Chandan R.R.; Mazumdar B.D.; Goyal N. (My University, 2025)
Due to the severe underwater environment, research into Underwater Wireless Sensor Networks is at its most undeveloped stage. Due to the restricted sensor batteries and significant variations in water parameters, like temperature, turbulence, flooding, pH, salinity, and others, this research is not as simple as it would seem. To increase node battery life and provide load balancing, several routing protocols are implemented. In this article, we propose the Effective Load Balancing with Sensor Injection routing method, which uses hop distance calculations to enable sensors to connect with sinks through other intermediary sensors. In order to communicate among sensors, localization-based routing protocol is employed. With the use of weight factor calculations, each node determines the minimal distance needed for connection to another node and calculates distance from the lowest hop node. This algorithm balances the load using the sensor injection approach. When weight factor of any node becomes high, it sends request to Network Management System (NMS) for load balancing. NMS directs Autonomous Underwater Vehicle for new sensor injection as neighbour of high factor node. Thus, by using this sensor injection method network lifetime gets increased. Simulation is carried out on NS 2.30 and improved results are obtained in comparison to existing schemes w.r.t., number of dead nodes and alive nodes at every round. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.